Studying the chronology of climate change near Akademik Vernadsky Station by determination of concentrations of chemical impurities in the glacier - Budnik, P.I.; Grishchenko, V. F.; Klishevich, G. V.; Curmei, N. D.; Makarenko, T. I. (Ukrainian Antarctic Journal, 2012)
The results of investigations of the chemical composition of Antarctic ice samples taken from glaciers are presented. Continuous analysis of the concentration of chemical elements over the entire depth of the glacier allows identify cold and warm periods along the entire period of time ranging from the formation of the glacier. Analysis of the number of annual layers in the same-size samples of ice as well as the annual average concentration in the layer, allows one to set periods with both higher and lower amount of atmospheric precipitations.